2019
DOI: 10.1371/journal.pone.0222361
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, tobacco and cannabis use are associated with job loss at follow-up: Findings from the CONSTANCES cohort

Abstract: BackgroundSubstance use is more prevalent among unemployed subjects compared to employed ones. However, quantifying the risk subsequent of job loss at short-term according to substance use remains underexplored as well as examining if this association persist across various sociodemographic and occupational positions previously linked to job loss. We examined this issue prospectively for alcohol, tobacco, cannabis use and their combination, among a large population-based sample of men and women, while taking i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 39 publications
1
21
1
6
Order By: Relevance
“…For some of the study population, the unexpected association between unemployment and seeking care for AUD might be attributable to job loss or difficulties finding a job due to alcohol consumption. This contrasts however with previous studies which found a positive association between job loss, unemployment and AUD [49,50], especially among people with a higher education level [51].…”
Section: Discussioncontrasting
confidence: 99%
“…For some of the study population, the unexpected association between unemployment and seeking care for AUD might be attributable to job loss or difficulties finding a job due to alcohol consumption. This contrasts however with previous studies which found a positive association between job loss, unemployment and AUD [49,50], especially among people with a higher education level [51].…”
Section: Discussioncontrasting
confidence: 99%
“…The added AUD characteristics beyond alcohol intake might contribute to the association observed between AUD and the risk of depressive symptoms. It has been suggested that AUD could lead to a decline in life circumstances, such as health impairment, mental breakdown, job loss, family disruption and illegal conduct , which might further lead to the development of depressive symptoms. Other possible explanations include the genetic theory that AUD presence increases the risk of depression by regulating neurotransmission function .…”
Section: Discussionmentioning
confidence: 99%
“…Concerns regarding adolescent cannabis use are supported by three streams of research. First, large-scale observational studies have shown that adolescent use is associated with many negative outcomes, including mental health problems (8)(9)(10)(11), misuse of alcohol and other drugs (8,11,12), cognitive impairment (13)(14)(15)(16), reduced socioeconomic attainment (11,17), and unemployment (18,19). Most studies find these associations become increasingly likely the earlier cannabis use is initiated.…”
mentioning
confidence: 99%